Respiratory syncytial virus assembly in epithelial cells and macrophages - Laxmi Ravi Iyer (2014)
Respiratory syncytial virus is an important respiratory virus which causes severe lower respiratory tract infections in infants, elderly and immunocompromised adults. According to WHO reports, lower respiratory tract infections contribute to an estimated 160,000 deaths annually and 64 million reported cases worldwide and have an impact which is comparable to that of non-pandemic influenza virus infections. Hence, development of a vaccine for RSV has been accorded topmost priority. We have been trying to study the interactions between the different virus glycoproteins – F, G and SH, and have showed that they form an oligomeric complex, through biotinylation and cross-linking studies. Also, a mechanism for RSV assembly and transmission involving the G protein and Actin has been proposed. We suggest that, on RSV infection, the G protein is localized to the surface of the infected cells into F-actin enriched structures. During the time of virus filament formation, i.e. around 12 hpi, there is a slight increase in the activated Cdc42 levels, which are then targeted to these sites of virus filament formation, causing localized changes in the Factin network , modifying it to form virus filament-like structures which then enables cell-cell transmission of RSV. Thus, we have found that G plays a pivotal role in initiating virus assembly and enabling cell-cell transmission through their association with actin. This was further confirmed using inhibitors such as cytochalasin D and Lovastatin, which is an HMGCoA inhibitor. The interaction between virus and host cell can divulge a lot of information about the way the virus hijacks the host cell processes, and knowledge of this can lead to development of possible anti-viral strategies. Here, we have characterized RSV infection in RAW 264.7 cells and pulmonary lung macrophages. Both could be efficiently infected with RSV A2. Several studies have suggested that disease severity is associated with an increase in pro-inflammatory cytokine response. Hence, we investigated the ability of RSV to induce pro-inflammatory cytokine response in RAW 264.7 cells and pulmonary lung macrophages. There was a significant increase in the pro-inflammatory cytokines namely IL-6, TNF-alpha, RANTES, MCP-1 etc. in the macrophages. It was also found that, lovastatin treatment could alleviate the proinflammatory cytokine response, and hence could possibly be used in the treatment of RSV infection.